Practicing Intertextuality in English as a Foreign Language: An Indonesian EFL Learner’s Experiences - Arlita, Chintya; Prasetya, Willy (Journal of English and Education (JEE), 2024)
The existing studies on intertextuality In Indonesia mainly focuses on the contexts of mass media and literature, so little is known about intertextuality within the context of higher education, not to mention the one involving multiple languages including English. The present study explored intertextuality practices of an Indonesian EFL learner. The data were collected through semi-structured interviews and analyzed thematically. The findings pointed out that the participant’s ability to practice intertextuality was highly influenced by his well-developed reading habit. Furthermore, it was indicated that intertextuality practices helped the participant better understand texts and their underlying aspects, find connection of texts with other discourses, and establish relevance of texts within real-life settings. By discussing how an Indonesian EFL learner practiced his intertextuality for academic and non-academic purposes in higher education, this study may provide as an empirical contribution for the growing body of research on intertextuality practices in Indonesia.